Solvability of mental health care in the Family Health Strategy: social representation of professionals and users - Maria Salete Bessa Jorge; Mardênia Gomes Ferreira Vasconcelos; Euton Freitas de Castro Junior; Levi Alves Barreto; Lianna Ramalho de Sena Rosa; Leilson Lira de Lima (SciELO, 2014)
Objective To aprehend the social representations about the solvability in mental health care with users of the Family Health Strategy and professionals of family health teams and of the Center for Psychosocial Care. Method A qualitative study using semi-structured interviews for data collection, and the Alceste software for analysis. This software uses the Hierarchical Descending Classification based on the examination of lexical roots, considering the words as units and providing context in the corpus. Results The representations emerge in two opposing poles: the users require satisfaction with care and the professionals realize the need for improvement of health actions. Although the matricial support in mental health and the home visits are developed, the barriers related to investment in health, continuing education and organization of care persist. Conclusion The different representations enable improvements in customer service, solvability of care and aggregate knowledge and practices in the expanded perspective of health needs in the family, social and therapeutic context.